2020
DOI: 10.1292/jvms.19-0235
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and cross-sectional detection of four bovine enteric viruses by multiplex- reverse transcription polymerase chain reaction: Identification of possible indicator viruses to assess biosecurity level at bovine farms

Abstract: It can be judged that if the detection frequency of prevalent pathogenic viruses decreases, biosecurity has been enhanced. To monitor bovine farm biosecurity levels, one-step multiplex reverse transcription polymerase chain reaction (RT-PCR) for the simultaneous detection of group A rotavirus (RVA), bovine torovirus (BToV), bovine enterovirus (BEV), and bovine coronavirus (BCV) was designed, with the aim of configuring candidates for "viral pathogen indicators". A total of 322 bovine fecal samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…All of those four viruses were also detected in farm A in Ibaraki prefecture [20]. Our previous results revealed that RVA was the primary agent among the positive samples obtained at the age of 3 weeks or below, while BEV was the primary among those obtained at an age over 3 weeks [20]. So in the present study, fecal samplings were separated by the age of calves (3 weeks or below and over 3 weeks).…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…All of those four viruses were also detected in farm A in Ibaraki prefecture [20]. Our previous results revealed that RVA was the primary agent among the positive samples obtained at the age of 3 weeks or below, while BEV was the primary among those obtained at an age over 3 weeks [20]. So in the present study, fecal samplings were separated by the age of calves (3 weeks or below and over 3 weeks).…”
Section: Introductionmentioning
confidence: 58%
“…Mixed infections usually make the disease worse than a single infection. BCV and BEV were detected continuously for several weeks in the same calves, however, RVA was detected only for several days [5,6,20].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations